The Economic Impact of Sawntimber Export Levy Removal on the Peninsular Malaysia's Economy - Puasa, Ahmad Fauzi (2005)
The global demand for wood-based products will continue to grow in line with increasing population and economic development especially in many developing countries. Despite this reason, the production of this primary industry has declined slowly in the last decade. The Malaysian wood-based supply has faced a deficit starting from 1995; from there on, wood-based products moved from a state of resource surplus to one of deficit in Malaysia. Realizing the problem of the supply of raw materials faced by the local furniture manufacturing industries, the Malaysian Government has imposed an export levy on wood-based products including sawntimber. This is to ensure an adequate supply of raw materials for the local manufacturers. However, the imposition of the export levy has indirectly suppressed the domestic wood market prices, which has eventually reduced the sawmillers' income. The Government has overlooked this root problem faced by the sawmilling industry, i.e. the suppression of domestic prices. If the Government is not sensitive to this problem, the sawmilling industry will eventually shrink due to insufficient supply of raw materials, in spite of the export levy. Based on this problem, the main objective of this study is to determine the effects of the sawntimber export levy removal and its implication on the Peninsular Malaysian economy. There are two types of model used for this study: an econometric model to determine the net welfare economic impacts, and an input-output model to investigate the total economic impacts resulting from sawntimber export levy removal on the Peninsular Malaysian economy. The empirical study from the econometric model shows that there is net positive social welfare economic impact on the society resulting from the sawntimber export levy removal. In fact, the input-output analysis manages to compute the total output, income and employment impacts on the Peninsular Malaysian economy as a result of the sawntimber export levy removal. Thus the removal of sawntimber export levy contributes significantly to the Peninsular Malaysian economy.